Realismo e violência em romances da literatura marginal-periférica brasileira : a representação da favela - Botton, André Natã Mello (2019)
In the outskirts of Brazilian cities there is a very intense cultural production. Literature, as one of the artistic manifestations, also fictionalizes this reality. However, the great difference between marginal-peripheral literature and the canonized one is the narrative construction, since the narrator voice can be identified with some of the slum’s inhabitants, and no longer the power-centered visions that look towards the margin, in other words, it is a literature produced by the periphery, to the periphery. Thus, the object of this dissertation is the new literary realism and violence studied from four books that represent the slums: Pedaços da Fome (1963), by Carolina Maria de Jesus, Capão Pecado (2000) by Ferréz, Becos da Memória (2006), by Conceição Evaristo, and Graduado em Marginalidade (2009), by Sacolinha. Throughout the analysis of the four novels, the guiding question is the way the slum is represented, thus considering violence and the new realism present in fiction. From a bibliographical point of view, the present paper summarizes the historical and social evolution of the slums, a space that will be considered as a constituent of the city. Then, there is a survey of literary materials that, throughout the history of the Brazilian literature, reveal the slums and its inhabitants. The third part of this paper consists of a theoretical revision about the concepts of "violence" and "new realism" as parameters of analysis of the four novels that constitute the corpus of this research. The new realism is much more concerned with representing social aspects that constitute life inside the slums - and not just a single subject - and which can go beyond the fictional universe. The representative game, in this way, would occur in three movements: reality-fiction-reality. Within this, the two traits - demand for presence and daily subjective awareness - presented by Schollhammmer (2009) are in a play of representation that comes from social reality to the subjective and returns to social reality. They do complement each other and help the narrative and allow other reflections from it, such as the study of violence. To consider the periphery as a heterogeneous whole is to perceive the multiplicity of stories that have contributed over time to assert itself in these spaces. These stories are being represented in the pages of literature arising from the Brazilian slums. By perceiving the literary texts within a whole, which is connected to some extent by aesthetic parameters, it can be said that fictionalizing the Brazilian slums is part of the new realism as literary and cultural expression. What marginal-peripheral literature has done is an attempt to present the slums seen from within, from a place without the stereotypes of the authors who represented it from the outside. Violence, while one of the characteristics present in the novels is not the only one, but one that stands out in the attempt to criticize imposed social models. The new realism would then appear as an aesthetic movement of criticism of a society divided and stigmatized by prejudice and social exclusion.